Health State Valuation in Iran: An Exercise on Cardiovascular Diseases Using Visual Analogue Scale Method - H Bakhshandeh; K Holakouie Naeini; H Zeraati; MH Forouzanfar; F Noohi; A Sadeghpour; A Alizadeh Diz; HR Sanati; F Abolhassani Shahreza (Tehran University of Medical Sciences, 2009)
Background: Disability Weights (DWs) are main components for computing summary measure of population health (SMPH) and economic studies. They are specific for each community, but there are no previous studies in Iran. In this study, we investigated the feasibility of health state valuation (HSV) in Iranian population. Methods: Twelve cardiologists in 3 sessions of expert panels, defined 25 states, related to cardiovascular diseases (3 major and 22 specific diseases). From January to March 2008, 80 persons in 4 groups including: physicians, patients, patients' families and general publics (each group 20), were interviewed and valuated the states, using visual analogue scale (VAS) method. SPSS® 15 for window® (SPSS Corporation, Chicago, Illinois) was used for statistical analysis. Results: Data showed that the defined health states had various severities. All the 4 groups ranked the "3 major-diseases" and "very-mild" and "very-severe" states, similarly. Non-physicians were not able to differentiate among "valvular-diseases" and "pacemakers" properly. The reliability of responses was acceptable. Conclusion: VAS is an appropriate and reliable method for HSV in Iranian population. Non-physicians' opinions can be consider in major cardiac diseases. Valuation of more specific situations must perform by physicians.